Step * 2 1 1 of Lemma weakly-safe-extension

.....assertion..... 
1. : ℕ ⟶ ℕ ⟶ ℙ
2. : ℕ
3. : ℕn ⟶ ℕ
4. weakly-safe-seq(R;n;s)
5. ¬(∀p,q:ℕ.
       (homogeneous(R;n 1;s.p@n)  homogeneous(R;n 1;s.q@n)  p <  (¬¬homogeneous(R;n 2;s.p@n.q@n 1))))
6. : ℕ
7. : ℕ
8. homogeneous(R;n 1;s.p@n)
9. homogeneous(R;n 1;s.q@n)
10. p < q
11. ¬homogeneous(R;n 2;s.p@n.q@n 1)
⊢ ¬¬(weakly-safe-seq(R;n 1;s.p@n) ∨ weakly-safe-seq(R;n 1;s.q@n))
BY
TACTIC:(Unfold `weakly-safe-seq` THEN (Subst' (n 1) THENA Auto)) }

1
1. : ℕ ⟶ ℕ ⟶ ℙ
2. : ℕ
3. : ℕn ⟶ ℕ
4. weakly-safe-seq(R;n;s)
5. ¬(∀p,q:ℕ.
       (homogeneous(R;n 1;s.p@n)  homogeneous(R;n 1;s.q@n)  p <  (¬¬homogeneous(R;n 2;s.p@n.q@n 1))))
6. : ℕ
7. : ℕ
8. homogeneous(R;n 1;s.p@n)
9. homogeneous(R;n 1;s.q@n)
10. p < q
11. ¬homogeneous(R;n 2;s.p@n.q@n 1)
⊢ ¬¬(w∃∞q.homogeneous(R;n 2;s.p@n.q@n 1) ∨ w∃∞q@0.homogeneous(R;n 2;s.q@n.q@0@n 1))


Latex:


Latex:
.....assertion..... 
1.  R  :  \mBbbN{}  {}\mrightarrow{}  \mBbbN{}  {}\mrightarrow{}  \mBbbP{}
2.  n  :  \mBbbN{}
3.  s  :  \mBbbN{}n  {}\mrightarrow{}  \mBbbN{}
4.  weakly-safe-seq(R;n;s)
5.  \mneg{}(\mforall{}p,q:\mBbbN{}.
              (homogeneous(R;n  +  1;s.p@n)
              {}\mRightarrow{}  homogeneous(R;n  +  1;s.q@n)
              {}\mRightarrow{}  p  <  q
              {}\mRightarrow{}  (\mneg{}\mneg{}homogeneous(R;n  +  2;s.p@n.q@n  +  1))))
6.  p  :  \mBbbN{}
7.  q  :  \mBbbN{}
8.  homogeneous(R;n  +  1;s.p@n)
9.  homogeneous(R;n  +  1;s.q@n)
10.  p  <  q
11.  \mneg{}homogeneous(R;n  +  2;s.p@n.q@n  +  1)
\mvdash{}  \mneg{}\mneg{}(weakly-safe-seq(R;n  +  1;s.p@n)  \mvee{}  weakly-safe-seq(R;n  +  1;s.q@n))


By


Latex:
TACTIC:(Unfold  `weakly-safe-seq`  0  THEN  (Subst'  (n  +  1)  +  1  \msim{}  n  +  2  0  THENA  Auto))




Home Index